Iktisāb al-Lugah al-‘Arabiyah ka al-Lugat al-tsānawiyah ladā Talāmidzi al-Madrasah - Huda, Mokhammad Miftakhul; Maskud, Maskud; Rachma, Anggiya (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2020)
This research is about the acquisition of Arabic as a second language of high school students at Darul Ulum Islamic Boarding School Jombang East Java. The type of research in this research is the Qualitative Research, because the result obtained is in the form of description data in the form of a word, phrase, sentence, etc. Qualitative research is a research method that does not need to design research hypotheses, nor do researchers use numbers in interpretation to produce. The results of this research are: Factors that support their success in the Arabic language acquisition is divided into two: internal factors and external factors. Internal factors are factors related to mental and psychiatric students at Darul Ulum Islamic Boarding School Jombang. While external factors relating to full support from madrasah leaders and teachers with the formation of the Language Club (LC), implementation of language programs), the diversity of methods in teaching Arabic, organizing activities and programs in language.